2014
DOI: 10.1007/s40266-014-0159-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Benzodiazepines and Association with Falls in Older People Admitted to Hospital: A Prospective Cohort Study

Abstract: Different BZDs may vary in their propensity to predispose to falls, with diazepam having the strongest association. The selection of particular BZDs for older patients should be carefully evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 58 publications
0
21
0
8
Order By: Relevance
“…BZDs remain the treatment of choice for the elderly; however, in contrast with the recommendations for younger adult populations, short half‐life BZDs reduce the risk of accumulation and the resulting adverse events, such as sedation and falls, in the elderly . Therefore, short half‐life BZDs are preferred for elderly patients (grade B).…”
Section: Resultsmentioning
confidence: 99%
“…BZDs remain the treatment of choice for the elderly; however, in contrast with the recommendations for younger adult populations, short half‐life BZDs reduce the risk of accumulation and the resulting adverse events, such as sedation and falls, in the elderly . Therefore, short half‐life BZDs are preferred for elderly patients (grade B).…”
Section: Resultsmentioning
confidence: 99%
“…However, data on whether different characteristics (as exposure duration, daily dose, and elimination half-life) lead to different risks are inconsistent. A study reported that the use of long-acting BZDs increases the risk of falls [16], whereas other studies have reported that the use of short-acting BZDs also increases this risk [17, 18]. In addition, another study indicated that dosage contributes more to the risk of falls than elimination half-life [19].…”
Section: Introductionmentioning
confidence: 99%
“…In older patients they have been associated with cognitive decline, dementia 3 and falls. 4,5 There is evidence of increased mortality with long-term use. 6 In February 2014, in response to increasing illicit use, alprazolam was rescheduled to Schedule 8.…”
Section: Introductionmentioning
confidence: 99%